1999
DOI: 10.1152/jn.1999.82.2.1059
|View full text |Cite
|
Sign up to set email alerts
|

Kainate Acts at Presynaptic Receptors to Increase GABA Release From Hypothalamic Neurons

Abstract: Recent reports suggest that kainate acting at presynaptic receptors reduces the release of the inhibitory transmitter GABA from hippocampal neurons. In contrast, in the hypothalamus in the presence of alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and N-methyl-D-aspartate (NMDA) receptor antagonists [1-(4-methyl-7,8-methylenedioxy-5H-2,3-benzodiazepine (GYKI 52466) and D,L-2-amino-5-phosphonopentanoic acid (AP5)], kainate increased GABA release. In the presence of tetrodotoxin, the frequency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…However, the use of novel benzodiazepine compounds (GYKI compounds), which act as selective antagonists of AMPA receptors (Paternain et al, 1995), has provided a means of demonstrating a distinct role of KARs in modulating synaptic transmission. Interestingly, several in vitro electrophysiological and pharmacological studies have shown that KARS mediate presynaptic effects on GABAergic and glutamatergic neurotransmission in various brain regions (Clarke et al, 1997;Lerma et al, 1997;Rodriguez-Moreno et al, 1997;Mulle et al, 1998;Rodriguez-Moreno and Lerma, 1998;Chittajallu et al, 1999;Liu et al, 1999;Min et al, 1999;Perkinton and Sihra, 1999;Chergui et al, 2000;Contractor et al, 2000;Frerking and Nicoll, 2000;Kamiya and Ozawa, 2000). Furthermore, the excitotoxic effects of KAR agonists were found to be greatly reduced in the CA3 region of the rat hippocampus after mossy fiber denervation (Debonnel et al, 1989).…”
Section: Abstract: Huntington's Disease; Excitotoxicity; Presynapticmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of novel benzodiazepine compounds (GYKI compounds), which act as selective antagonists of AMPA receptors (Paternain et al, 1995), has provided a means of demonstrating a distinct role of KARs in modulating synaptic transmission. Interestingly, several in vitro electrophysiological and pharmacological studies have shown that KARS mediate presynaptic effects on GABAergic and glutamatergic neurotransmission in various brain regions (Clarke et al, 1997;Lerma et al, 1997;Rodriguez-Moreno et al, 1997;Mulle et al, 1998;Rodriguez-Moreno and Lerma, 1998;Chittajallu et al, 1999;Liu et al, 1999;Min et al, 1999;Perkinton and Sihra, 1999;Chergui et al, 2000;Contractor et al, 2000;Frerking and Nicoll, 2000;Kamiya and Ozawa, 2000). Furthermore, the excitotoxic effects of KAR agonists were found to be greatly reduced in the CA3 region of the rat hippocampus after mossy fiber denervation (Debonnel et al, 1989).…”
Section: Abstract: Huntington's Disease; Excitotoxicity; Presynapticmentioning
confidence: 99%
“…Interestingly, recent evidence indicates that activation of GluR6-containing presynaptic kainate receptors facilitates glutamate exocytosis from cerebral cortex nerve terminals in a synaptosome preparation (Perkinton and Sihra, 1999). Similarly, kainate acts at presynaptic receptors to increase GABA release from hypothalamic neurons (Liu et al, 1999). However, kainate was found to downregulate GABAergic transmission in the rat hippocampus (Rodriguez-Moreno et al, 1997).…”
Section: Potential Functions Of Presynaptic Striatal Kainate Receptorsmentioning
confidence: 99%
“…In the present study, 20-100 jiM DOI induced only an enhancement of evoked NMDA receptor-mediated field 62 A. Chen et al / Neuroscience 119 (2003) [53][54][55][56][57][58][59][60][61][62][63] and intracellular recorded potentials in tlie amygdala. This effect was blocked both by the 5-HT2 antagonist ketanserin and by the S-HTzc receptor selective antagonist RSI02221.…”
Section: Enhancement Of Nmda-receptor Functions By Doimentioning
confidence: 50%
“…The biphasic effect of DOB was interpreted as an activation of protein kinase C (PKC) at low DOB concentration and calmodulin kinase 11 at high DOB concentration (Arvanov et al, 1999). Rahman and Neuman interpreted the same phenomenon as desensitization, but had to invoke more than one mechanism to explain its biphasic nature (Rahman and Neuman, 1993).In the present study, 20-100 jiM DOI induced only an enhancement of evoked NMDA receptor-mediated field 62 A. Chen et al / Neuroscience 119 (2003) [53][54][55][56][57][58][59][60][61][62][63] and intracellular recorded potentials in tlie amygdala. This effect was blocked both by the 5-HT2 antagonist ketanserin and by the S-HTzc receptor selective antagonist RSI02221.…”
mentioning
confidence: 65%
See 1 more Smart Citation